A comparative analysis of biomedical research ethics regulation systems in Europe and Latin America with regard to the protection of human subjects. Issue 12 (26th August 2010) - Lamas, Eugenia; Ferrer, Marcela; Molina, Alberto; Salinas, Rodrigo; Hevia, Adriana; Bota, Alexandre; Feinholz, Dafna; Fuchs, Michael; Schramm, Roland; Tealdi, Juan-Carlos; Zorrilla, Sergio
Abstract : The European project European and Latin American Systems of Ethics Regulation of Biomedical Research Project (EULABOR) has carried out the first comparative analysis of ethics regulation systems for biomedical research in seven countries in Europe and Latin America, evaluating their roles in the protection of human subjects. We developed a conceptual and methodological framework defining 'ethics regulation system for biomedical research' as a set of actors, institutions, codes and laws involved in overseeing the ethics of biomedical research on humans. This framework allowed us to develop comprehensive national reports by conducting semi-structured interviews to key informants. These reports were summarised and analysed in a comparative analysis. The study showed that the regulatory framework for clinical research in these countries differ in scope. It showed that despite the different political contexts, actors involved and motivations for creating the regulation, in most of the studied countries it was the government who took the lead in setting up the system. The study also showed that Europe and Latin America are similar regarding national bodies and research ethics committees, but the Brazilian system has strong and noteworthy specificities.